2017
DOI: 10.1016/j.mimet.2017.01.006
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of the efficiency and uncertainty of skimmed milk flocculation for the simultaneous concentration and quantification of water-borne viruses, bacteria and protozoa

Abstract: In this study, the use of skimmed milk flocculation (SMF) to simultaneously concentrate viruses, bacteria and protozoa was evaluated. We selected strains of faecal indicator bacteria and pathogens, such as Escherichia coli and Helicobacter pylori. The viruses selected were adenovirus (HAdV 35), rotavirus (RoV SA-11), the bacteriophage MS2 and bovine viral diarrhoea virus (BVDV). The protozoa tested were Acanthamoeba, Giardia and Cryptosporidium. The mean recoveries with q(RT)PCR were 66% (HAdV 35), 24% (MS2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…The concentration was corrected with a Beta distribution, with recoveries previously described specifically for the SMF. For HAdV data was previously described with an average recovery of 66% (Table 1) (Gonzales-Gustavson et al, 2017), and for NoV GII, we used data from a previous study where 8 water samples were spiked showing an average recovery of 41% (Unpublished results). The recoveries when testing 50 mL raw sewage samples have been evaluated also in previous studies in the laboratory and presented equivalent results (Calgua et al, 2013b).…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…The concentration was corrected with a Beta distribution, with recoveries previously described specifically for the SMF. For HAdV data was previously described with an average recovery of 66% (Table 1) (Gonzales-Gustavson et al, 2017), and for NoV GII, we used data from a previous study where 8 water samples were spiked showing an average recovery of 41% (Unpublished results). The recoveries when testing 50 mL raw sewage samples have been evaluated also in previous studies in the laboratory and presented equivalent results (Calgua et al, 2013b).…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…This variation may be justified by the complex nature of the raw sewage samples. Previous studies have shown important variation rates in viral recovery between concentration methods [28][29][30] and once RVA and MS2 do not have the same characteristics (dsRNA vs. bacteriophage ssRNA), the efficiency of recovery for both viruses is not expected to be correlated.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary data obtained by our research group in a study analysing different concentration methods for the detection of SARS-CoV-2 in wastewater from Catalonia (Spain), using MS2 as a process control, showed no statistically significant differences ( p -value of the ANOVA test: 0.332) between the quantitative data (RT-qPCR) produced by the three viral concentration methods both for SARS-CoV-2 and for MS2. Four wastewater samples were concentrated using the SMF protocol [ 35 ] with an initial sample volume of 250 mL, the CeUF of 70 mL of the sample with Centricon® Plus-70 100 kDa (CeUF) [ 20 ] and a new and quick 80-mL ultrafiltration protocol using the automatic Concentrating Pipette (CP-Select™) from Innovaprep using 150 kDa ultrafiltration tips ( www.innovaprep.com ) ( Figure 2 ). Debris was removed before the ultrafiltration by pelleting using centrifugation at 4750× g for 30 min.…”
Section: Sars-cov-2 In Wastewater Studiesmentioning
confidence: 99%
“…Despite the proposed viral concentration methods for SARS-CoV-2 or generally for CoV, extensively reviewed by others, the organic flocculation, has been also used for the concentration of viruses in water including enveloped viruses. The enveloped virus, bovine viral diarrhoea virus (BVDV), presented mean recoveries of 15% when tested with qPCR and 0.7% when tested for infectivity, but acid pH (for approximately 16 h) that is used in the SMF protocol seems to reduce the infectivity, as the log 10 ratio RT-qPCR/infectivity for that virus was 2.03 [ 35 , 38 , 39 ]. The same observation has been described for PEG precipitation methods, which disrupt the lipid bilayers and thus are not optimal for recovering infective enveloped viruses [ 18 , 40 ].…”
Section: Concentration Of Other Enveloped Viruses With Pandemic Potenmentioning
confidence: 99%